Order-disorder transformation in the Ni-4.49 at.% Al alloy - Adorno, A. T.; Garlipp, W.; Cilense, M.; Silva, RAG (Elsevier B.V., 2006)
The order-disorder transformation in the Ni-4.49 at.% Al alloy was studied using electrical resistivity measurements, microhardness measurements, differential scanning calorimetry (DSC) and transmission electron microscopy (TEM). The results confirmed the ordering behavior expected for Ni-Al dilute alloys and the suggested relation between resistivity changes and microhardness changes with antiferromagnetic spin ordering. The higher value obtained for the activation energy of vacancy migration was associated with a decrease in the Al concentration gradient near solute-depleted regions. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: electrical properties; metals and alloys; atomic order transformation